The Role of Social Media on Adolescent Behavior in Accessing Pornographic Content - Ni Kadek Ayu Dwi Utami Ds; Komang Srititin Agustina; Ni Rai Sintya Agustini; Lina Darmayanti Bainuan (JURNAL KEBIDANAN KESTRA (JKK), 2025)
The development of the era followed by an increase in technological sophistication has resulted in easy access to information through various media including social media. Teenagers as one of the most active groups of people using technology are highly exposed to the influence of social media. This phenomenon has both positive and negative impacts on the behavior and mindset of adolescents, especially in accessing pornographic content. This study aims to look at the relationship between social media exposure and adolescent behavior in accessing pornographic content. This study used a cross-sectional analytic research approach with a total sample size of 76 samples. The sampling method used was probability proportional to size. The data source in this study is primary data obtained directly from adolescents through filling out questionnaires. Adolescents who easily access information media and have consumed pornography amounted to 48.7%, while adolescents who have difficulty accessing information media and have consumed pornography amounted to 83.8%, with a p value of 0.001. There is a relationship between information media access and pornography consumption. Despite the government's efforts to restrict pornographic content, this does not prevent teenagers from consuming pornographic content. They look for other alternatives in the form of media to access the content as stated by the teenagers in this study. Teenagers admitted that pornographic content is mostly accessed through websites, social media, whatsapp groups and telegrams. They access pornographic videos and photos more than pornographic stories/comics or porn games.